Effect of a topical polyherbal formulation for premature ejaculation: A randomized triple-blind placebo-controlled trial. Issue 3 (September 2021) - Moosavi-Asil, Seyed Hamed; Ahmadian-Attari, Mohammad Mahdi; Shirzad, Meysam; Yekaninejad, Mir Saeed; Nikoobakht, Mohammad Reza; Karimi, Mehrdad
Highlights: Persian medicine as a complementary treatment discipline suggests different natural products for premature ejaculation. A topical oil containing black cumin oil, olive oil and frankincense was evaluated as a randomized controlled trial. The drug had no significant adverse effect. There was no remarkable change in total IELT and PEDT scores. The drug significantly improved premature ejaculation frequency and interpersonal difficulty items. Abstract: Background: The purpose of this study was to evaluate the efficacy of a topical polyherbal formulation (frankincense, black cumin oil, olive oil) on premature ejaculation (PE). Methods: 76 patients with PE were assigned into two parallel groups to receive a drug or placebo. At the baseline and the end of study, patients were asked to measure intravaginal ejaculatory latency time (IELT) during at least three sexual intercourses and premature ejaculation diagnostic tool (PEDT) was also performed. All participants were asked to apply drug or placebo topically on the genital area every night for three weeks. Analysis of covariance was used to compare the mean outcomes changes. Results: A total of, 66 patients in two groups completed the study. Baseline IELT and PEDT scores were 32.79 ± 3.56 s and 18.5 ± 0.65 in the drug group and 29.35 ± 3.57 s and 19.57 ± 0.52 in the placebo group. At the end of the study, IELT and PEDT scores were 68.42 ± 13.7 s and 17.46 ± 0.74 in the drug group, and 44.67 ± 7.73 s and 19 ± 0.61 in the placebo group. There was no significant change in IELT and PEDT scores. Baseline two items of PEDT score i.e. PE frequency and Interpersonal difficulty were 3.96 ± 0.26 and 4.03 ± 0.18 in the drug group and 4.54 ± 0.15 and 4.18 ± 0.11 in the placebo group. At the end of the study, PE frequency and Interpersonal difficulty were 4 ± 0.22 and 3.6 ± 0.23 in the drug group and 4.66 ± 0.12 and 4.18 ± 0.13 in the placebo group. Both of them were significant (P = 0.04 in both items). Conclusion: In spite of insignificant changes between drug and control groups in total scores of PEDT and IELT, the drug improved PE frequency and interpersonal difficulty items. Therefore, the drug effectiveness in some important items, suggests that the product can be used as a topical supplementary agent in the treatment of PE.